Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s40279-015-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oestrogen Treatment on Skeletal Response to Exercise in the Hips and Spine in Postmenopausal Women: A Meta-Analysis

Abstract: Our findings indicate that oestrogen treatment significantly increases the skeletal response to exercise training in both the hips and the spine in postmenopausal women, which implies that the combination of oestrogen administration and exercise may generate greater effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In this population, hormone replacement improves muscle mass and function by improving muscle repair, and the response to feeding and exercise. Bone mass and function is also improved by HRT (Zhao et al, 2015). The problem is that long term HRT use is associated with decreased tendon cross-sectional area, especially in an active population (Cook et al, 2007).…”
Section: Practical Considerations To Maximize Performance and Minimizmentioning
confidence: 99%
“…In this population, hormone replacement improves muscle mass and function by improving muscle repair, and the response to feeding and exercise. Bone mass and function is also improved by HRT (Zhao et al, 2015). The problem is that long term HRT use is associated with decreased tendon cross-sectional area, especially in an active population (Cook et al, 2007).…”
Section: Practical Considerations To Maximize Performance and Minimizmentioning
confidence: 99%
“…In part support of this notion, a meta-analysis of six intervention trials in postmenopausal women aged 52 to 68 years found that combined hormone replacement therapy (HRT) and exercise was associated with greater improvements in femoral neck and lumbar spine BMD than exercise alone. 63 The mixed findings with regard to the effects of weightbearing exercise on bone may be related to differences in the exercises prescribed and/or technique used, the non-progressive nature of some programs, a failure to incorporate multi-directional or novel loading activities and/or compliance issues associated with other comorbidities (e.g. pain from osteoarthritis).…”
Section: Weight-bearing Impact Exercisementioning
confidence: 99%
“…However, because mechanical responsiveness decreases with age, determining whether these differences are due solely to estrogen status is difficult. Estrogen treatment and exercise increase bone mass more than exercise alone among postmenopausal women, but how these differences compare to premenopausal women is unclear …”
Section: Introductionmentioning
confidence: 99%
“…Estrogen treatment and exercise increase bone mass more than exercise alone among postmenopausal women, but how these differences compare to premenopausal women is unclear. 17 Animal models of menopause and hormone depletion are useful tools for studying the role of estrogen and other hormones in mechanical adaptation, and include ovariectomy (OVX) and orchidectomy (ORX). In rats, for instance, estrogen treatment reduced skeletal responsiveness to exercise and mechanical loading, 18 and OVX-induced estrogen loss increased responsiveness.…”
Section: Introductionmentioning
confidence: 99%